"Humanized" Stem Cell Culture Techniques: The Animal Serum Controversy - Chandana Tekkatte; Gency Ponrose Gunasingh; K. M. Cherian; Kavitha Sankaranarayanan (Hindawi Limited, 2011)
Cellular therapy is reaching a pinnacle with an understanding of the potential of human mesenchymal stem cells (hMSCs) to regenerate damaged tissue in the body. The limited numbers of these hMSCs in currently identified sources, like bone marrow, adipose tissue, and so forth, bring forth the need for their in vitro culture/expansion. However, the extensive usage of supplements containing xenogeneic components in the expansion-media might pose a risk to the post-transplantation safety of patients. This warrants the necessity to identify and develop chemically defined or "humanized" supplements which would make in vitro cultured/processed cells relatively safer for transplantation in regenerative medicine. In this paper, we outline the various caveats associated with conventionally used supplements of xenogenic origin and also portray the possible alternatives/additives which could one day herald the dawn of a new era in the translation of in vitro cultured cells to therapeutic interventions.